Membrane glycoproteins involved in neurite fasciculation (The Rockefeller University Press, 1987)
Lectin affinity chromatography combined with mAb production was used to identify chick neural cell surface molecules related to L1 antigen, a mouse neural glycoprotein implicated in cell-cell adhesion (Rathjen, F. G., and M. Schachner, 1984, EMBO (Eur. Mol. Biol. Organ.) J., 3:1-10). A glycoprotein, G4 antigen, isolated by mAb G4 from adult chick brain is described which comprises a major 135-kD component, a minor doublet at 190 kD, and diffusely migrating bands at 80 and 65 kD in SDS PAGE. This molecule is structurally related to mouse L1 antigen according to NH2-terminal amino acid sequence (50% identity) as well as the behavior of its components in two-dimensional IEF/SDS PAGE gels. A second chicken glycoprotein, F11 antigen, was isolated from adult chick brain using mAb F11. This protein has also a major 135-kD component and minor components at 170 kD and 120 kD. Both immunotransfer analysis with polyclonal antibodies to mAb G4 and to mAb F11 isolate and the behavior on IEF/SDS PAGE gels indicates that the major 135-kD component of F11 antigen is distinct from G4 antigen components. However, the 135-kD component of F11 antigen shares with G4 antigen and the neural cell adhesion molecule (NCAM) the HNK-1/L2 carbohydrate epitope. In immunofluorescence studies, G4 and F11 antigenic sites were found to be associated mainly with the surface of process-bearing cells, particularly in fiber-rich regions of embryonic brain. Although Fab fragments of polyclonal antibodies to mAbs G4 or F11 immunoaffinity isolate only weakly inhibit the Ca2+-independent aggregation of neural cells, they strongly inhibit fasciculation of retinal axons. Together these studies extend the evidence that bundling of axons reflects the combined effects of a group of distinct cell surface glycoproteins.